Lipidome of midbody released from neural stem and progenitor cells during mammalian cortical neurogenesis - Arai, Yoko; Sampaio, Julio L; Wilsch-Bräuninger, Michaela; Ettinger, Andreas W; Haffner, Christiane; Huttner, Wieland B (Frontiers in Cellular Neuroscience, 2015)
Midbody release from proliferative neural progenitor cells is tightly associated with the neuronal commitment of neural progenitor cells during the progression of neurogenesis in the mammalian cerebral cortex. While the central portion of the midbody, a cytoplasmic bridge between nascent daughter cells, is engulfed by one of the daughter cell by most cells in vitro, it is shown to be released into the extracellular cerebrospinal fluid in vivo in mouse embryos. Several proteins have been involved in midbody release; however, few studies have addressed the participation of the plasma membrane’s lipids in this process. Here, we show by Shotgun Lipidomic analysis that phosphatydylserine (PS), among other lipids, is enriched in the released midbodies compared to lipoparticles and cellular membranes, both collected from the cerebrospinal fluid of the developing mouse embryos. Moreover, the developing mouse embryo neural progenitor cells released two distinct types of midbodies carrying either internalized PS or externalized PS on their membrane. This strongly suggests that phagocytosis and an alternative fate of released midbodies exists. HeLa cells, which are known to mainly engulf the midbody show almost no PS exposure, if any, on the outer leaflet of the midbody membrane. These results point towards that PS exposure might be involved in the selection of recipients of released midbodies, either to be engulfed by daughter cells or phagocytosed by non-daughter cells or another cell type in the developing cerebral cortex.